Debate on sexual minority rights in Africa : a comparative analysis of the situation in South Africa, Uganda, Malawi and Botswana - Van der Poll, Letitia (University of Pretoria, 2011)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2010.